KEPEMIMPINAN MULTIDIMENSI KEPALA MADRASAH DARI PERSPEKTIF GURU - Rahman, Bujang (Universitas Islam Negeri Raden Intan Lampung, 2014)
THE MULTIDIMENSIONAL LEADERSHIP OF MADRASAH LEADER IN TEACHER’S PERSPECTIVE: The quality of the madrasa leadership has contributed greatly to the success of education in the school. As the leader of the organization/ educational institution, the main role of the madrasah leader is as a manager and an administrator. As an instructional leader, the main role of the madrasah leader is as an educator and a supervisor. This paper aims to explain how a madrasah leader performs his/her role in the leadership of madrasah in the four dimension of leaderships and its implications for the effectiveness of education in madrasah. A total of 120 teachers from 16 madrasah (MTs and MA) with varied backgrounds were involved in this study. With the Cronbach Alpha of the research instrument0.917, empirically the research revealed that madrasah leader role as an administrator dominated over the roles as a manager and supervisor which were relatively similar. Meanwhile, the role as an educator seemed to be very weak. This indicates that madrasah leaders need to enhance their role as instructional leaders as this has direct impacts on the establishment of conducive academic atmosphere at madrasah. Ideally, to achieve the optimized outcomes of education in madrasah, these four dimensions should be run in a balanced manner.